Secured IoT Data Transmission with Enhanced Integrated Encryption Techniques with Blockchain Technology - S. Joseph
The Internet of Things (IoT) revolutionizes how we interact with smart devices. However, ensuring security in IoT systems presents complex challenges due to their centralized architecture and inherent limitations. The increasing attention towards blockchain technology stems from its decentralized structure, transparency, immutable records, and cryptographic hash functions, particularly when combined with the Internet of Things (IoT). Cryptographic hash algorithms are essential to blockchain technology, ensuring secure data transmission by linking private and public keys through mathematical functions. Existing cryptographic algorithms typically produce variable hash values accessible to a single node and support input key sizes up to 128 bytes. However, larger key sizes can reduce transaction accuracy, lower key entropy, decrease throughput, and increase transaction complexity. Conversely, smaller key sizes increase vulnerability to attacks. To overcome these challenges, several advancements have been proposed. A modified key signature scheme extends the key size to 256 bytes, achieving 82.6% accuracy, a time complexity of 1.68 nanoseconds, and a throughput of 15.24 kilobytes per 200 nanoseconds. However, this scheme operates on a single-node basis, limiting accessibility. These advancements aim to bolster security in IoT data transmission by integrating encryption techniques with blockchain technology. The performance of the modified signature scheme is analyzed through transaction parameters such as accuracy, time complexity, throughput, and hash output with cryptographic hash functions like SHA224, SHA256, SHA384, SHA512, MD5, SHA3-224, SHA3-256, SHA3-384, SHA3-512, and ECDSA. From this analysis, the elliptic curve cryptography algorithm gives higher accuracy and throughput with less time complexity.